Genetic variation and racial admixture in the Miskito of the southern Mosquito Shore, Nicaragua - Azofeifa, Jorge (1998)
A survey of the electrophoretic variation at eleven loci red-blood cell enzymes. hemoglobins and serum proteinswas performed on a sample of 59 Miskitos stemming from the southernmost part of the Mosquito shore of Nicaraagua. Seven loci. ALB. a-o p-, y-globins, LDHA. LDHB, and TPI were monomorphic; API. CP. HP"and TF were polymorphic representing a proportion of polymorphic loci (P) of 0.364 and an average heterozygosity (H) of 0.077. Both values are wjthin a range covered by ten Chibchan tribes of Costa Rica and Panama evaluated for the same loci -(P) = 0.364-0.182; (H) = 0.104-0.052-. The data a1lowed an estimation of minimum (mI = 0.0), mean (mm = 7.34) and maximum (m, = 21.9) pereentages of racial admixture with blacks. For eomparison, admixture was a1so calculated from the data -mainly blood groups- of a previous survey performed in 1960 by A. Matson and his group on a sample of a region near the border between Nicaragua and Honduras; results (mI = 6.05), (mm = 11.0) and (m, = 18.1). The values showed no statistieal difference. for the mean estimates, under the assumption that the non-Indian a1leles are Poisson-distributed (P=0.42). The documentation ofwhat is supposed to be the beginning of the racial admixture of the Miskito with blaeks in 1641 permitted the caleulation of the rate of admixture per generation -generation length: 27 years-; its maximum value lies between 1.68 and 1.91 percent. These results indicate that the Miskito gene pool has a preponde